THE SCREEN EFFECT OF THE MAGIC MIRROR IN ALFRED LORD TENNYSON’S POEM “THE LADY OF SHALOTT” AND PRE-RAPHAELITE ILLUSTRATIONS / ЭКРАННОСТЬ МАГИЧЕСКОГО ЗЕРКАЛА В ПОЭМЕ А. ТЕННИСОНА «ЛЕДИ ИЗ ШАЛОТТ» И ИЛЛЮСТРАЦИЯХ ПРЕРАФАЭЛИТОВ - NIKIFOROVA A.E. / НИКИФОРОВА А.Е. (Наука телевидения)
The relation between screen culture and imagery in Alfred Lord Tennyson’s poem “The Lady of Shalott” as well as in Pre-Raphaelite illustrations and paintings to the poem are analyzed in the article. The image of Lady depicts the total dependence on a magical “screen”, which, in itself, is a mirror. The author draws attention to the fact that a fairy behaves like a dependent human being, a passive perceiving individual, more typical for the mass media era. The works by Dante Gabriel Rossetti, John Everett Millais and William Holman Hunt, which transmit the poem’s episodes and consider to different extents the image of a mirror similar to a screen are studied. The author also analyzes Henry Peach Robinson’s staged photography “The Lady of Shalott” which resembles closely a black-and-white film frame. The Pre-Raphaelite illustrations and paintings are in some ways more traditional than the images in Tennyson’s poem. The image of the mirror fades into insignificance. Only in Hunt’s drawings and paintings we can see this magiс object clearly. However, the threads of a tapestry wound around the Lady’s body in the paintings by Hunt and John William Waterhouse present the most successful visual image associated with the poem. Illustrations with the predominance of female figures and disregard for Lancelot’s image highlight the connection between the pre-screen motifs with the theme of female self-affirmation and crisis of romantic masculinity.